1975
DOI: 10.1080/00039896.1975.10666773
|View full text |Cite
|
Sign up to set email alerts
|

Toxicology of High-Fired Beryllium Oxide Inhaled by Rodents

Abstract: Several groups of male and female rats and hamsters were exposed by inhalation to an aerosol of BeO particles calcined at 1000 C. Initial alveolar depositions ranged from 12 mug to 160mug Be. The alveolar retention half-life for BeO was approximately six months. Only the pulmonary lymph nodes accumulated detectable amounts of translocated BeO. Early alterations were seen in the alveolar macrophages, which were subsequently converted to histiocytic cells that accumulated in subpleural and peribronchiolar granul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
3
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 7 publications
5
3
0
Order By: Relevance
“…Low urinary concentration for BeO-F was in accordance with other animal studies which have demonstrated very slow pulmonary clearance for this species (Sanders et al, 1975;Rhoads and Sanders, 1985). It is usually reported that the retention of Be in the lung can play an important role in the development of lung infl ammation (Salehi et al, 2009), but this is not obvious in our study.…”
Section: −1supporting
confidence: 92%
“…Low urinary concentration for BeO-F was in accordance with other animal studies which have demonstrated very slow pulmonary clearance for this species (Sanders et al, 1975;Rhoads and Sanders, 1985). It is usually reported that the retention of Be in the lung can play an important role in the development of lung infl ammation (Salehi et al, 2009), but this is not obvious in our study.…”
Section: −1supporting
confidence: 92%
“…Similar peripheral accumulations of dust have been observed in the rodent lung following exposure to beryllium oxide (Sanders and Cannon, 1975) and in rodent, dog and human lungs following exposure to plutonium oxide (Clarke and Bair, 1964;Sanders and Dagle, 1974;Voelz et al, 1976). If asbestos fibres are transported in a similar manner to the periphery of the human lung, this could be an important factor in the aetiology both of asbestosis, which generally appears to affect subpleural areas first (Becklake, 1976) and of asbestos-induced mesothelial tumours.…”
supporting
confidence: 56%
“…These data are similar to those reported by others (55,56,58) in which foreign-body type granulomatous inflammation of the lung occured after inhalation exposure of rats to Be materials. In these previous reports, lymphocytes were not a significant component of the lesions, and granuloma formation either did not occur or was limited to that associated with cholesterol cleft formation, an indicator of cell necrosis.…”
Section: Chronic Beryllium Diseasesupporting
confidence: 93%